Avaliação da atividade farmacológica de substâncias purificadas a partir de plantas do semi-árido brasileiro no modelo de asma brônquica - Senra, Juliana Fraga Vasconcelos (2007)
Asthma is a chronic inflammation of airways associated with a Th2 immune response, involving eosinophils, mast cells, IgE and several soluble mediators. The available drugs are not very efficient, being the corticosteroids the most used, despite their side effects. In this work we investigated the efficacy of four pure substances, isolated from plants found in the brazilian semi-arid region, in the treatment of bronchic asthma in BALB/c mice immunized with ovalbumin. Treatment with physalins B or F did not revert the inflammatory response. In contrast, the administration of lupeol or umbeliferona caused the reduction of eosinophils and other inflammatory cells in the lung and of the production of mucus and pro-inflammatory cytokines (IL-4, IL-5 and IL-13) similar to the effect of dexamethasone. Our findings reinforce the importance of the brazilian flora as a rich source of biomolecules. The investigation of the mechanisms of action of these molecules may contribute for the development of new drugs for the treatment of this pathology.